PENGGUNAAN MEDIA GAMBAR BERSERI BERBASIS DIORAMA 3D DALAM UPAYA MENINGKATKAN MINAT MEMBACA SISWA KELAS 1 SD N TEGALSARI 5 BATANG - Alifia Hani Maulida; Ade bagus Primadoni, Dian Kusumawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Reading is considered a basic knowledge that must be possessed by someone, by reading someone can learn various things, starting from science, history, culture, to various other aspects of life. By reading can open one's insight and expand one's knowledge about various things in the world. The purpose of this study is to determine the impact of using serial image media based on 3D dioramas in increasing the reading interest of elementary school students. With the hope that if students' reading interest increases, student learning outcomes will also increase. This study uses a classroom action research method where the subjects of the study were 31 students of grade I of Tegalsari 5 Elementary School. The results of the study show an increase in students' reading interest by using serial image media based on 3D dioramas.